Capital account liberalization and financial sector stability - Ishii, Shogo...[et al.] (IMF WashingtonUS, 2002)
Analyzes the linkages between capital account liberalization and other policies influencing financial sector stability. Develops an operational framework for sequencing and coordinating capital account liberalization with other policies aimed at maintaining financial sector stability. Focuses especially on policies aimed at developing sound domestic financial structure.